Metabolism meets inflammation: lactate and lactylation in inflammatory pathogenesis - Xin Huang; Yaqiao Zhu; Ruiming Guo; Wei Qiu; Fuchun Fang (Oral Science and Homeostatic Medicine, 2026)
Abstract Once regarded primarily as a glycolytic by-product, lactate is increasingly recognized as an active signaling metabolite involved in a broad spectrum of diseases. In parallel, lysine lactylation, a recently described post-translational modification, has been linked to the regulation of cellular functions, immune responses, and metabolic reprogramming. This review summarizes the metabolic mechanisms underlying lactate production and lactylation within the inflammatory microenvironment, and discusses how the lactate-lactylation axis relates to the dynamic “alteration-exudation-proliferation” trajectory of inflammation. We outline how lactate functions beyond bioenergetics to influence gene-regulatory programs and immune-cell behavior through lactylation, thereby shaping the alteration, exudation and proliferation phases of inflammation. Evidence from sepsis, inflammatory bowel disease, osteoarthritis, and periodontitis is highlighted to illustrate disease-relevant roles and to frame current knowledge gaps. These four diseases were selected as representative inflammatory or infection-related conditions because they share key pathological features, including dysregulated inflammatory responses, immune-metabolic reprogramming, lactate accumulation, and emerging evidence for the involvement of lactylation. Finally, we discuss future directions, emphasizing that integrating single-cell multi-omics with high-specificity reagents will be important for resolving the spatiotemporal features of lactylation and for advancing translational applications. A deeper understanding of lactate signaling and the lactate-lactylation axis may inform new strategies for the diagnosis and treatment of inflammation-associated diseases.